AKSES KETERSEDIAN AIR BERSIH BAGI MASYARAKAT DI DESA TURIKAMASENG KECAMATAN BONTOA KABUPATEN MAROS - Murniati Murni; Ibrahim Ibrahim; Romlah Romlah; Nurul Hidayah (Social Landscape Journal, 2023)
The research objectives were to find out 1) Availability of clean water for the people in Tunikamaseang Village, Bontoa District, Maros Regency. 2) Access to clean water for the community in Tunikamaseang Village, Bontoa District, Maros Regency. 3) The efforts of the local government and the community in overcoming clean water problems in Tunikamaseang Village, Bontoa District, Maros Regency. The type of research used is descriptive qualitative. Data collection techniques are observation, interviews, and documentation. Data analysis was carried out, namely preparing data, reflecting on data, coding data, dividing coding results, interpreting and interpreting data. The results of the study show that: 1) The availability of clean water in Tunikamaseang village is minimal, the community only relies on rainwater and PDAM water as a source of clean water. As for other water sources used, but the quality is not clean enough, such as drilled wells, dug wells, pond water, and reservoir water. The constraints are the lack of available clean water, namely the provision of clean water has not been a priority, community sanitation facilities and behavior are still lacking and the factor of low rainfall. 2) The level of access to clean water for the people in Tunikamaseang village is at the basic level of access. Distance and travel time to get clean water between 100-1000m or 5-30 minutes. Meanwhile, the price of clean water is relatively expensive, namely Rp. 50,000,-/m3 or about 18 times the price of PDAM clean water. The difficulty of access to clean water is due to the very minimum available facilities and the poor financial condition of the people. 3) The efforts of the local government in overcoming clean water problems in Tunikamaseang village are distributing reservoirs and making proposals for the procurement of clean water assistance aimed at the Regional Government. While the community's efforts are making piped connections to clean water, maintaining water sources, saving on the use of clean water, making rainwater reservoirs and private boreholes.Keywords: Clean Water; Access; Availability